Prevalence, Awareness, Treatment and Control of Diabetes Among Elderly Persons in an Urban Slum of Delhi - Arvind Kumar Singh; Kalaivani Mani; Anand Krishnan; Praveen Aggarwal; Sanjeev Kumar Gupta (Wolters Kluwer Medknow Publications, 2012)
Background : The increasing proportion of elderly persons is contributing to an increase in the prevalence of diabetes. The residents of urban slums are more vulnerable due to poverty and lack of access to health care. Objective: To estimate the prevalence of diabetes in elderly persons in an urban slum and to assess their awareness, treatment and control of this condition. Materials and Methods : All persons aged 60 years and above, residing in an urban slum of Delhi, were included in this cross-sectional community- based study. Data were collected on sociodemographic variables. The participants' awareness and treatment of diabetes was recorded. Their fasting blood sugar was estimated using an automated glucometer. Diabetes was diagnosed if fasting blood glucose was ≥126 mg/dL, or if the participant was taking treatment for diabetes. Impaired fasting blood glucose was diagnosed if fasting blood glucose was 110-125 mg/dL. Results: Among the 474 participants studied, the prevalence of diabetes was estimated to be 18.8% (95% CI 15.3-21.5). It decreased with increasing age, and was higher among women. The prevalence of impaired fasting blood glucose was 19.8% (95% CI 16.3-23.7). It was higher among women. One-third of the diabetic participants were aware of their condition; two-thirds of these were on treatment and three-fourths of those on treatment had controlled fasting blood sugar level. The awareness, treatment and control were better among women. Conclusions : Diabetes is common among elderly persons in urban slums. Its magnitude and low awareness warrant effective public health interventions for their treatment and control.